Persistent ambipolar heptacenes and their redox species: dedicated to Professor Holger Braunschweig on the occasion of his 60th birthday - Zeitter, Nico; Hippchen, Nikolai; Maier, Steffen; Rominger, Frank; Dreuw, Andreas; Freudenberg, Jan; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2022)
Sixfold TIPS-ethynylation combined with fourfold bromination of the armchair edges furnishes a long-lived, soluble heptacene; π-extension via Stille coupling accesses a persistent tetrabenzononacene. Both types of acenes were stabilized best by double TIPS-ethynylation on every other benzene ring. Tetrabromoheptacene is an ambipolar transistor material (up to 0.036 cm2 V−1 s−1 n-channel), which was corroborated by generation of its monoanion and monocation.
Online veröffentlicht am 04. April 2022
Gesehen am 13.12.2022
Keywords: Festschrift